Pet attachment, spiritual well-being, and stress in muslims: A mediation model - Hermawati, Nisa; Azizah, Nur'aini; Noviani, Rifa Shaumi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2025)
Stress is a common challenge faced by Muslim university students, particularly in navigating academic, social, and developmental pressures. To mitigate these burdens, students seek emotional support from companion animals, such as cats. This study examined whether spiritual well-being mediates the relationship between pet attachment and perceived stress among Muslim university students who are cat owners, recruited through convenience sampling at the Zoom Vet Team Animal Clinic to ensure methodological transparency. A quantitative approach was used with 188 respondents completing the Lexington Attachment to Pets Scale (LAPS), the Spiritual Well-Being Scale, and the Perceived Stress Scale (PSS). Mediation analysis (PROCESS Model 4) revealed that pet attachment was significantly associated with lower perceived stress (total effect: B = –0.18, p < .001). Pet attachment also significantly predicted higher spiritual well-being (B = 0.52, p < .001), which in turn predicted lower stress levels (B = –0.22, p < .001). The indirect effect was significant (ab = –0.11, 95% CI [–0.17, –0.06]), indicating partial mediation, while the direct effect remained significant but reduced (B = –0.07, p = .041). These findings demonstrate that pet attachment functions as both a psychological and spiritual coping resource, reducing stress directly and indirectly through enhanced spiritual well-being. The study highlights the importance of incorporating spiritual dimensions into stress and coping models for Muslim populations and supports the development of culturally sensitive mental health interventions that recognize human–animal bonds as potential protective factors.